Enhancing microbial fuel cell performance with carbon powder electrode modifications for low-power sensors modules - Al-badani, Mohammed Adel; Chong, Peng Lean; Lim, Heng Siong (International Journal of Renewable Energy Development, 2024)
Microbial Fuel Cell (MFC) is a promising technology for harnessing energy from organic compounds. However, the low power generation of MFCs remains a significant challenge that hinders their commercial viability. In this study, we reported three distinct modifications to the stainless-steel mesh (SSM), carbon cloth, and carbon felt electrodes using carbon powder (CP), a mixture of CP and ferrum, and a blend of CP with sodium citrate and ethanol. The MFC equipped with an SSM and CP anode showed a notable power density of 1046.89 mW.m-2. In comparison, the bare SSM anode achieved a maximum power density of 145.8 mW m-2. Remarkably, the 3D-modified SSM with a CP anode (3D-SSM-CP) MFC exhibited a substantial breakthrough, attaining a maximum power density of 1417.07 mW m-2. This achievement signifies a significant advancement over the performance of the unaltered SSM anode, underscoring the effectiveness of our modification approach. Subsequently, the 3D-SSM-CP electrode was integrated into single-chamber MFCs, which were used to power a LoRaWAN IoT device through a power management system. The modification methods improved the MFC performance while involving low-cost and easy fabricating techniques. The results of this study are expected to contribute to improving MFC's performance, bringing them closer to becoming a practical source of renewable energy.